2019
DOI: 10.1590/s0004-2803.201900000-33
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Adult Liver Transplantation in a Referral Center in Southern Brazil

Abstract: BACKGROUND: Liver transplantation (LTx) is the primary and definitive treatment of acute or chronic cases of advanced or end-stage liver disease. Few studies have assessed the actual cost of LTx categorized by hospital unit. OBJECTIVE: To evaluate the cost of LTx categorized by unit specialty within a referral center in southern Brazil. METHODS: We retrospectively reviewed the medical records of 109 patients undergoing LTx between April 2013 and December 2014. Data were collected on demographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
2
0
6
Order By: Relevance
“…In a systematic study, it was observed that in eight studies reintubation rate in patients who were extubated immediately after transplantation was from 0 to 11% and in patients who were extubated in the conventional way in the ICU it was from 0 to 36%. 22 The reintubation generates high hospital costs; the average LTx cost in Brazil is around R$ 17,367, corresponding to 31.9% in the surgical unit and 25.3% in ICU. 23 Prolonged mechanical ventilation may also increase right ventricular after load and even induce venous congestion of the liver graft, especially in those with pre-existing tricuspid regurgitation and raised pulmonary artery pressures (which is not uncommon in end-stage liver disease patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic study, it was observed that in eight studies reintubation rate in patients who were extubated immediately after transplantation was from 0 to 11% and in patients who were extubated in the conventional way in the ICU it was from 0 to 36%. 22 The reintubation generates high hospital costs; the average LTx cost in Brazil is around R$ 17,367, corresponding to 31.9% in the surgical unit and 25.3% in ICU. 23 Prolonged mechanical ventilation may also increase right ventricular after load and even induce venous congestion of the liver graft, especially in those with pre-existing tricuspid regurgitation and raised pulmonary artery pressures (which is not uncommon in end-stage liver disease patients).…”
Section: Discussionmentioning
confidence: 99%
“…23 Prolonged mechanical ventilation may also increase right ventricular after load and even induce venous congestion of the liver graft, especially in those with pre-existing tricuspid regurgitation and raised pulmonary artery pressures (which is not uncommon in end-stage liver disease patients). 24 When comparing the reintubated group with the non-orotracheal reintubation (Retot) group, it can be observed that the ICU time values (14 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] days and 4 [5][6][7] days, < 0.001), mechanical ventilation time (6 [5-19] and 1 [1-3] days < 0.001) and mortality 57.9% vs. 19.1% were significantly higher in the reintubated group.…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo sistemático, observou-se que em oito estudos a taxa de reintubação em pacientes que foram extubados imediatamente após o transplante foi de 0 a 11% e em pacientes que foram extubados de forma convencional na UTI foi de 0 a 36%. 22 A reintubação gera altos custos hospitalares; o custo médio do THx no Brasil gira em torno de R$ 17.367, correspondendo a 31,9% na unidade cirúrgica e 25,3% na UTI. 23 A ventilação mecânica prolongada também pode aumentar após carga no ventrículo direito e até mesmo induzir a congestão venosa do enxerto hepático, especialmente naqueles com insuficiência tricúspide preexistente e pressão arterial pulmonar elevada (o que não é incomum em pacientes com doença hepática terminal).…”
Section: Discussionunclassified
“…Entretanto, esse tipo de doação apresentou custos mais elevados, apesar de possuir um tempo médio de internação menor, se comparado com o procedimento provindo de doadores vivos, o que diverge de outros estudos 11 . A análise dos custos deve levar em consideração variáveis relacionadas a gravidade da doença de cada paciente 8 , bem como os orçamentos e as políticas de compras de insumos de cada hospital 12 . O Sistema Nacional de Transplante (SNT) do Brasil passa por problemas organizacionais como 13 : falta de acesso a nível nacional de exames para diagnosticar morte encefálica; impasses na manutenção e transporte de órgãos; problemas na gestão das Centrais de Notificação e Captação e Distribuição de Órgãos(CNCDO's) 2 .…”
Section: Discussionunclassified